2020
DOI: 10.21470/1678-9741-2019-0392
|View full text |Cite
|
Sign up to set email alerts
|

Tea Grape Reduces Abdominal Aortic Occlusion-Induced Lung Injury

Abstract: Introduction Ischemia-associated mortality caused by aortic cross-clamps, as in ruptured abdominal aorta aneurysm surgeries, and reperfusion following their removal represent some of the main emergency conditions in cardiovascular surgery. The purpose of our study was to examine the potential protective effect of tea grape against aortic occlusion-induced lung injury using biochemical, histopathological, immunohistochemical, and quantitative analyses. Methods Thirty-two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…Although the tissue damage mechanism has not been fully explained in I/R studies based on clamping the infra‐renal aorta, increasing free oxygen radical production resulting from lipid peroxidation has been reported to lead to oxidative stress. [ 7,9,30 ] Şener et al reported an increase in liver tissue MDA levels, while GSH levels decreased, following I/R of the infrarenal aorta. [ 33 ] We also observed elevated MDA levels and decreased GSH levels in liver tissue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the tissue damage mechanism has not been fully explained in I/R studies based on clamping the infra‐renal aorta, increasing free oxygen radical production resulting from lipid peroxidation has been reported to lead to oxidative stress. [ 7,9,30 ] Şener et al reported an increase in liver tissue MDA levels, while GSH levels decreased, following I/R of the infrarenal aorta. [ 33 ] We also observed elevated MDA levels and decreased GSH levels in liver tissue.…”
Section: Discussionmentioning
confidence: 99%
“…I/R studies based on clamping the infrarenal aorta have reported increased caspase‐3 expression leading to apoptosis, together with oxidative stress. [ 1,9,10,12 ] Özkeçeci et al also observed that caspase‐3 expression increased and resulted in apoptosis. [ 34 ] Similarly, in the present study, cleaved caspase‐3 positivity increased in both intra‐ and interlobular hepatocytes following I/R.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The procedures during the determination of the experimental groups (control, I/Rep, I/Rep+solvent/dimethyl sulfoxide [DMSO], I/Rep+RES), anesthesia applications, carotid artery and jugular vein cannulations, vascular clamping in the infrarenal abdominal aorta (IAA) were performed as described previously. [ 7 , 8 ] In the I/Rep+RES group, 10 mg/kg RES was applied intraperitoneally 15 min before the clamps were placed in the IAA and immediately before the clamps were removed. To the I/Rep+DMSO group, 10 mg/kg DMSO was given intraperitoneally, and the same amount of saline was given to the I/Rep group (Table 1 ).…”
Section: Methodsmentioning
confidence: 99%